2021
DOI: 10.3389/fphar.2020.593693
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Pharmacology-Based Approach for Evaluating the Potential Effects of Purslane Seed in Diabetes Mellitus Treatment Using UHPLC-LTQ-Orbitrap and TCMIP V2.0

Abstract: Portulaca oleracea L., known as the “vegetable for long life,” is an annual succulent herb that is widely distributed worldwide. Many clinical and experimental studies have demonstrated that purslane seed (MCXZ) can be used as an adjunctive and alternative therapy for the treatment of diabetes mellitus (DM). However, the underlying active constituents and pharmacological mechanisms through which MCXZ exerts effects in DM remain unclear. In the present study, we confirmed that MCXZ treatment resulted in hypogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…The potential targets of the compounds identified in RSGB were predicted using the TCM target prediction and functional analysis module of TCMIP v2.0 ( http://www.tcmip.cn/ )[ 12 14 ]. The prediction accuracy was set to 0.70 (medium and high similarity).…”
Section: Methodsmentioning
confidence: 99%
“…The potential targets of the compounds identified in RSGB were predicted using the TCM target prediction and functional analysis module of TCMIP v2.0 ( http://www.tcmip.cn/ )[ 12 14 ]. The prediction accuracy was set to 0.70 (medium and high similarity).…”
Section: Methodsmentioning
confidence: 99%
“…The Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP, http://tcmspw.com/tcmsp.php ) [ 18 ] was utilized to identify the chemical constituents of 11 Traditional Chinese Medicines screening process for active components in AGNHW relied on an oral drug concentration (OB) ≥ 30% and drug-like drugs (DL) ≥ 0.18, yielding a total of 60 effective chemical components after elimination of duplicates ( Supplementary Table S1 ). Based on the AGNHW component collection results, a research platform grounded on the Integrative Pharmacology-based Research Platform of Traditional Chinese Medicine (TCMIP V2.0, http://www.tcmip.cn/TCMIP/index.php ) [ 19 , 20 ] was implemented. The fundamental principle of target prediction is to utilize MedChem Studio (version 3.0) software to detect the structural similarity between the two-dimensional structure of chemical components in DrugBank and approved certified drugs, and use the Tanimoto coefficient to score their similarities.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, research about purslane seeds is arising and mostly focus on its potential anti-hyperglycemic effects [117][118][119]. A study in 2021 showed that purslane seeds can lower blood glucose levels, potentially affect phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1), TNF, PPAR-γ, and other targets associated with insulin resistance and inflammation through the actions of various chemical components including genistein, levodopa, and daidzein etc [117].…”
Section: Anti-hyperglycemic Effectsmentioning
confidence: 99%